Optical laminate and picture display unit using optical laminate
By using active energy ray curing adhesive in the optical layer to control the thickness variation and curing shrinkage of the adhesive layer, the uneven display problem of thin liquid crystal display equipment is solved, and a thinner and even display optical layer and display equipment are realized.
Patent Information
- Application Number
- JP2023122821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
Existing thin liquid crystal display devices are prone to uneven display at different viewing angles, especially the thin linear pink color visible under three-wavelength light sources.
An optical layer laminate including a polarizing layer and a retardation layer is used to coat the adhesive layer with an active energy ray curing adhesive on the polarizing layer, and the thickness variation of the adhesive layer is controlled to be within 0.16 μm, and the relationship between T×S≦17 is satisfied by adjusting the thickness T of the adhesive layer and the curing shrinkage rate S is satisfied, thereby suppressing the interference phenomenon of the optical layer.
It effectively suppresses the uneven display phenomenon, especially the thin linear pink display uneven display under the three-wavelength light source, achieving a thinner optical layer and display device.
Smart Images

Figure 2025018808000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and an image display device using the optical laminate. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) have rapidly become widespread. In many image display devices, an optical laminate including a retardation film (e.g., an anti-reflection film in which a polarizing plate and a retardation film are integrated) is used. In recent years, as the demand for thinner image display devices has increased, the demand for thinner optical laminates has also increased. In order to reduce the thickness of optical laminates, the retardation layer (retardation film), which contributes greatly to the thickness, has been made thinner. A representative example of a thin retardation film is a film in which a liquid crystal compound is oriented and the oriented state is fixed (hereinafter referred to as a liquid crystal film). Since the birefringence (Δn) of a liquid crystal compound is significantly larger than that of a resin, the thickness of the liquid crystal film to obtain a desired in-plane retardation can be made significantly smaller than that of a stretched resin film. However, image display devices using optical laminates containing liquid crystal films may exhibit display unevenness (specifically, a phenomenon in which a thin line of particularly noticeable pink color is visible in the absorption axis direction of the polarizer) depending on the viewing environment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-222282 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-described conventional problems, and its main object is to provide an optical laminate including a liquid crystal alignment cured layer and capable of suppressing specific display unevenness when applied to an image display device.
Means for Solving the Problems
[0005] [1] An optical laminate according to one embodiment of the present invention has a polarizing plate including a polarizer and a retardation layer laminated on the polarizing plate via an adhesive layer; the retardation layer includes a first liquid crystal alignment cured layer and a second liquid crystal alignment cured layer in this order from the polarizing plate side; the retardation layer has a circular polarization function or an elliptical polarization function as a whole and has a relationship of Re(450) < Re(550) < Re(650); the thickness variation in a 10 cm × 10 cm region of the adhesive layer is 0.16 μm or less. [2] An optical laminate according to another embodiment of the present invention has a polarizing plate including a polarizer and a retardation layer laminated on the polarizing plate via an adhesive layer; the retardation layer includes a first liquid crystal alignment cured layer and a second liquid crystal alignment cured layer in this order from the polarizing plate side; the retardation layer has a circular polarization function or an elliptical polarization function as a whole and has a relationship of Re(450) < Re(550) < Re(650); when the thickness of the adhesive layer is T (μm) and the curing shrinkage rate of the adhesive constituting the adhesive layer is S (%), T × S ≦ 17 is satisfied. [3] In the above [2], the thickness variation in a 10 cm × 10 cm region of the adhesive layer is 0.16 μm or less. [4] In any one of the above [1] to [3], the adhesive layer is composed of an active energy ray curable adhesive. [5] In any one of the above [1] to [4], the thickness of the first liquid crystal alignment cured layer is 1.7 μm or less. [6] According to another aspect of the present invention, an image display device is provided. The image display device includes the optical laminate of any one of the above [1] to [5].
Effects of the Invention
[0006] According to an embodiment of the present invention, it is possible to realize an optical laminate that includes a liquid crystal alignment solidified layer and is capable of suppressing specific display unevenness when applied to an image display device. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation of a film measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation of a film measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d(nm) is the thickness of the film. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction of a film measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction of a film measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d(nm) is the thickness of the film. (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5) Angle When referring to an angle in this specification, unless otherwise specified, the angle includes angles in both clockwise and counterclockwise directions.
[0010] A. Optical laminate FIG. 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 100 in the illustrated example has a polarizing plate 10 and a retardation layer 20. The polarizing plate 10 and the retardation layer 20 are laminated via an adhesive layer 30. The polarizing plate 10 typically includes a polarizer 11 and protective layers 12 and 13 disposed on both sides of the polarizer 11. Depending on the purpose, at least one of the protective layers 12 and 13 may be omitted. Therefore, the polarizing plate may be a so-called double-protection polarizing plate, a so-called single-protection polarizing plate, or may be composed of only the polarizer. In one embodiment, the polarizing plate may be a single-protection polarizing plate with the protective layer 13 omitted.
[0011] The retardation layer 20 includes a first liquid crystal alignment cured layer 21 and a second liquid crystal alignment cured layer 22 in order from the polarizing plate 10 side. The first liquid crystal alignment cured layer 21 and the second liquid crystal alignment cured layer 22 are laminated via any suitable adhesive layer (not shown: hereinafter may be referred to as an interlayer adhesive layer). By using the liquid crystal alignment cured layer as the retardation layer, a desired in-plane retardation can be realized with a thickness significantly thinner than that of a stretched film of a resin film. As a result, significant thinning of the optical laminate can be achieved. The retardation layer 20 as a whole (as a laminate of the first liquid crystal alignment cured layer 21 and the second liquid crystal alignment cured layer 22) has a circular polarization function or an elliptical polarization function and has a relationship of Re(450) < Re(550) < Re(650). In one embodiment, the retardation layer as a whole may have an Nz coefficient of, for example, 0.30 to 0.70. In this specification, the "liquid crystal alignment cured layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "liquid crystal alignment cured layer" is a concept that includes an alignment cured layer obtained by curing a liquid crystal monomer.
[0012] In one embodiment of the present invention, the thickness variation of the adhesive layer 30 in a 10 cm x 10 cm region is 0.16 μm or less. The thickness variation is preferably 0.13 μm or less, more preferably 0.10 μm or less, even more preferably 0.07 μm or less, particularly preferably 0.05 μm or less, and particularly preferably 0.03 μm or less. The smaller the thickness variation, the more preferable, and the lower limit may be, for example, 0.01 μm. The thickness variation in such a range can be achieved, for example, by adjusting the formulation of the adhesive constituting the adhesive layer (substantially the number, type, combination, amount of monofunctional and polyfunctional components, etc.) and / or by adjusting the application method of the adhesive. The adhesive constituting the adhesive layer will be described in Section D below. As the application method of the adhesive, preferably, gravure coating and slot die coating can be mentioned.
[0013] In another embodiment of the present invention, when the thickness of adhesive layer 30 is T (μm) and the cure shrinkage rate of the adhesive constituting adhesive layer 30 is S (%), the thickness T and the cure shrinkage rate S satisfy the following formula. T×S≦17 T×S is preferably 15 or less, more preferably 13 or less, even more preferably 10 or less, particularly preferably 8 or less, and particularly preferably 7 or less. The lower limit of T×S may be, for example, 2, or may be, for example, 3. T×S can be an index of thickness variation, and if T×S is in such a range, thickness variation can be well suppressed. If only the thickness T is reduced, problems related to adhesion (e.g., peeling) often occur. If only the cure shrinkage rate S is reduced, the elastic modulus of the adhesive increases (the adhesive becomes hard), and as a result, stress relaxation upon impact becomes insufficient, making peeling more likely to occur.
[0014] The optical laminate may have a configuration in which the above-mentioned embodiments are combined. That is, in the optical laminate, the thickness variation may be equal to or less than the above-mentioned predetermined value, and T×S may be equal to or less than the above-mentioned predetermined value.
[0015] In examining further thinning of an optical laminate including a liquid crystal alignment solidified layer as a retardation layer, the present inventors have found a new problem that an image display device using an optical laminate including a liquid crystal alignment solidified layer as a retardation layer may cause a specific display unevenness depending on the viewing environment. Specifically, the present inventors have found that a phenomenon (sometimes called linear unevenness) in which a thin line with a particularly noticeable pink color is visible throughout the entire display in the absorption axis direction of a polarizer may occur in reflection under a three-wavelength light source. Furthermore, the present inventors have intensively studied suppression of such linear unevenness, and as a result, have found that linear unevenness can be suppressed by suppressing interference of the optical laminate. In addition, the present inventors have found that interference of the optical laminate can be suppressed by making the thickness variation in a predetermined region of the adhesive layer 0.16 μm or less and / or by making the thickness T of the adhesive layer and the curing shrinkage rate S of the adhesive constituting the adhesive layer satisfy the relationship T×S≦17, thereby successfully suppressing linear unevenness, and have completed the present invention. That is, such an effect by the embodiment of the present invention solves a problem newly found when considering further thinning of an optical laminate including a liquid crystal alignment solidified layer as a retardation layer, and is an unexpected excellent effect. It goes without saying that the embodiment of the present invention can suppress the display unevenness that has been recognized in the past.
[0016] The adhesive layer 30 is typically made of an active energy ray curable adhesive. The active energy ray curable adhesive has the advantages of excellent adhesion, durability (e.g., suppression of peeling under high temperature and / or high humidity environments), and productivity. The thickness T of the adhesive layer is preferably 1.8 μm or less, more preferably 1.5 μm or less, even more preferably 1.2 μm or less, particularly preferably 1.0 μm or less, and particularly preferably 0.8 μm or less. The lower limit of the thickness T of the adhesive layer may be, for example, 0.3 μm. The curing shrinkage rate S of the adhesive constituting the adhesive layer 30 is preferably 15% or less, more preferably 12% or less, even more preferably 11% or less, and particularly preferably 9% or less. The lower limit of the curing shrinkage rate S may be, for example, 3%, or may be, for example, 5%. If the thickness T and the curing shrinkage rate S are in such ranges, it is easy to set T×S to the desired range.
[0017] In the optical laminate, the total thickness from the first liquid crystal alignment solidified layer to the second liquid crystal alignment solidified layer is preferably 20 μm or less, more preferably 3 μm to 10 μm. According to the embodiment of the present invention, the problem of linear unevenness newly found in the optical laminate including a very thin liquid crystal alignment solidified layer can be solved. If the total thickness from the first liquid crystal alignment solidified layer to the second liquid crystal alignment solidified layer is in the above-mentioned range, the total thickness from the polarizing plate to the second liquid crystal alignment solidified layer (the substantial total thickness of the optical laminate excluding the thickness of the adhesive for bonding to the image display panel) can be, for example, 100 μm or less, or, for example, 30 μm to 80 μm.
[0018] For practical purposes, the optical laminate has a pressure-sensitive adhesive layer (not shown) as the outermost layer on the second liquid crystal alignment solidified layer side (image display panel side), and can be attached to the image display panel. In this case, it is preferable that a release liner is temporarily attached to the surface of the pressure-sensitive adhesive layer until the optical laminate is used. By temporarily attaching the release liner, the pressure-sensitive adhesive layer is protected and the optical laminate can be formed into a roll.
[0019] The components of the optical laminate will be specifically described below.
[0020] B. Polarizing plate B-1.Polarizer The polarizer 11 is typically made of a polyvinyl alcohol (PVA) resin film containing a dichroic material (e.g., iodine). Examples of PVA resins include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.
[0021] The PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin. With this configuration, a polarizer having desired mechanical strength can be obtained. The amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, based on 100% by weight of the entire PVA-based resin. If the amount is within this range, a polarizer having better mechanical strength can be obtained.
[0022] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of the halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA-based resin. In the manufacturing method described below, the halide can be blended in a coating liquid that forms a PVA-based resin layer, which is a precursor of the polarizer, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be increased, and therefore a polarizer having excellent optical properties (typically, both a high polarization degree and a high single transmittance) can be realized.
[0023] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.0% to 46.0%, and more preferably 42.0% to 45.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. According to the embodiment of the present invention, even if the single transmittance is in the above range, the degree of polarization can be maintained in such a range.
[0024] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. By combining such a thin polarizer with a liquid crystal alignment solidified layer, it is possible to significantly reduce the thickness of the optical laminate. Furthermore, if the thickness of the polarizer is within the above range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0025] The polarizer can be produced by any appropriate method. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0026] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as PVA films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0027] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0028] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. In addition, by simultaneously increasing the orientation of the PVA in advance, problems such as a decrease in the orientation of the PVA or dissolution when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be disturbed and the orientation can be reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0029] B-2.Protective layer The protective layers 12 and 13 are made of any suitable resin film. Representative materials for the resin film include cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as polynorbornene, (meth)acrylic resins, polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, and polycarbonate resins. Representative examples of (meth)acrylic resins include (meth)acrylic resins having a lactone ring structure. (Meth)acrylic resins having a lactone ring structure are described in, for example, JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084. These publications are incorporated herein by reference. From the viewpoint of ease of processing into irregular shapes, etc., cellulose-based resins are preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, cycloolefin-based resins and (meth)acrylic resins are preferred.
[0030] The optical laminate is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to a surface treatment as necessary. Examples of the surface treatment include hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment. Furthermore, the protective layer 12 may be subjected to a treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarizing function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the optical laminate can be suitably applied to image display devices that can be used outdoors.
[0031] In one embodiment, the protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.
[0032] The thickness of each of the protective layers 12 and 13 is preferably 10 μm to 80 μm, more preferably 12 μm to 40 μm, and further preferably 15 μm to 35 μm. When the protective layer 12 is surface-treated, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.
[0033] C. Retardation layer As described above, the retardation layer 20 includes a first liquid crystal alignment cured layer 21 and a second liquid crystal alignment cured layer 22 in order from the polarizer side. Further, as described above, the retardation layer 20 has a circular polarization function or an elliptical polarization function as a whole (as a laminate of the first liquid crystal alignment cured layer 21 and the second liquid crystal alignment cured layer 22), and has a relationship of Re(450) < Re(550) < Re(650). Regarding the description of the retardation layer in this section, simply referring to the "retardation layer" means explaining it as a whole, and simply referring to the "liquid crystal alignment cured layer" means explaining the first liquid crystal alignment cured layer and the second liquid crystal alignment cured layer together.
[0034] For the retardation layer 20, Re(550) is preferably 100 nm to 200 nm, more preferably 110 nm to 180 nm, still more preferably 120 nm to 170 nm, and particularly preferably 130 nm to 150 nm. If Re(550) of the retardation layer is in such a range, the retardation layer can exhibit a good circular polarization function or elliptical polarization function in combination with a polarizer.
[0035] The retardation layer 20 has a relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer 20 preferably exhibits an inverse dispersion wavelength dependence in which the retardation value increases according to the wavelength of the measurement light. With such a configuration, a good antireflection function can be realized in a very wide wavelength band. Re(450) / Re(550) is, for example, more than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and still more preferably 0.8 to 0.9. Re(650) / Re(550) is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1.
[0036] In one embodiment, the retardation layer 20 may have an Nz coefficient of, for example, 0.30 to 0.70 as described above. Therefore, the retardation layer 20 exhibits a refractive index characteristic of nx>nz>ny. With such a configuration, it is possible to effectively prevent reflection in oblique directions, and the anti-reflection function can be achieved over a wide viewing angle. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and even more preferably 0.45 to 0.55.
[0037] Examples of the liquid crystal compound used in the liquid crystal alignment solidified layer include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable (i.e., liquid crystal monomer). If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it. Here, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal alignment solidified layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes that are specific to liquid crystal compounds. As a result, the liquid crystal alignment solidified layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0038] In one embodiment, the liquid crystal alignment solidified layer may be formed using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or acid generated from a photopolymerization initiator. As the liquid crystal monomer, for example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc., can be used. Specific examples of such polymerizable mesogenic compounds include LC242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC3767 (trade name) from Wacker-Chem.
[0039] The mechanism by which the liquid crystal compound exhibits liquid crystallinity may be thermotropic or lyotropic. The liquid crystal phase may be nematic or smectic. From the viewpoint of ease of production, the liquid crystallinity is preferably thermotropic nematic liquid crystal.
[0040] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0041] The birefringence Δn of the liquid crystal alignment solidified layer is preferably 0.06 or more, more preferably 0.08 or more, even more preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn may be, for example, 0.13, or may be, for example, 0.12. If Δn is in such a range, a desired in-plane retardation can be realized with a very thin thickness. As a result, it becomes possible to further thin the liquid crystal alignment solidified layer and the optical laminate, which can ultimately contribute to a significant thinning of the image display device.
[0042] The liquid crystal alignment solidified layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value changes very little depending on the wavelength of the measurement light.
[0043] The first liquid crystal alignment solidified layer 21 can typically function as a λ / 2 plate, and the second liquid crystal alignment solidified layer 22 can typically function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal alignment solidified layer is preferably 150 nm to 300 nm, more preferably 200 nm to 270 nm, and even more preferably 220 nm to 260 nm; the Re(550) of the second liquid crystal alignment solidified layer is preferably 100 nm to 200 nm, more preferably 110 nm to 160 nm, and even more preferably 120 nm to 140 nm. The thickness of the first liquid crystal alignment solidified layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. In one embodiment, the thickness of the first liquid crystal alignment solidified layer can be, for example, 2.0 μm to 4.0 μm. In another embodiment, the thickness of the first liquid crystal alignment solidified layer is preferably 1.7 μm or less, more preferably 1.6 μm or less, and even more preferably 1.5 μm or less. In this case, the thickness of the first liquid crystal alignment solidified layer may be, for example, 1.3 μm or more. Thus, according to the embodiment of the present invention, the thickness of the first liquid crystal alignment solidified layer can be made thinner than before, while suppressing linear unevenness. The thickness of the second liquid crystal alignment solidified layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. Specifically, the thickness can be, for example, 0.8 μm to 2.5 μm. The angle between the slow axis of the first liquid crystal alignment solidified layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 14° to 16°; the angle between the slow axis of the second liquid crystal alignment solidified layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 74° to 76°. In addition, the order of arrangement of the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer may be reversed, and the angle between the slow axis of the first liquid crystal alignment solidified layer and the transmission axis of the polarizer and the angle between the slow axis of the second liquid crystal alignment solidified layer and the transmission axis of the polarizer may be reversed.
[0044] The refractive index of the liquid crystal alignment solidified layer can vary depending on the composition that forms the liquid crystal alignment solidified layer (substantially the type of liquid crystal compound, the type, number, combination, amount of additives, etc.). The refractive index n of the first liquid crystal alignment solidified layer LC1 and the refractive index n of the second liquid crystal alignment solidified layerLC2 may be the same or different from each other (the refractive index n LC1 may be larger, and the refractive index n LC2 The refractive index n of the first liquid crystal alignment layer may be larger. LC1 The refractive index n of the second liquid crystal alignment solidified layer is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. LC2 The refractive index n of the first liquid crystal alignment solidified layer is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. LC1 and the refractive index n of the second liquid crystal alignment solidified layer LC2 The refractive index n of the first liquid crystal alignment solidified layer may be the opposite. LC1 and the refractive index n of the second liquid crystal alignment solidified layer LC2 The absolute value of the difference between the refractive index and the cured adhesive layer may be, for example, 0.00 to 0.20. The refractive index of the liquid crystal alignment solidified layer typically conforms to the composition of the liquid crystal alignment solidified layer to obtain desired optical properties. As a result, linear unevenness may occur. According to an embodiment of the present invention, the thickness variation in a predetermined region of the adhesive layer is set to 0.16 μm or less, and / or the thickness T of the adhesive layer and the curing shrinkage rate S of the adhesive constituting the adhesive layer satisfy the relationship T×S≦17, thereby suppressing linear unevenness.
[0045] A side-chain type thermotropic liquid crystal polymer may be introduced into the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer (substantially the liquid crystal composition forming these). The introduction of a side-chain type thermotropic liquid crystal polymer can act to homeotropically align (vertically align) the liquid crystal monomer. As a result, the nz of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be increased, and as a result, the Nz coefficient of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be set to the desired range. Finally, the Nz coefficient of the retardation layer can be set to the desired range without providing a positive C plate described later.
[0046] As the side-chain type thermotropic liquid crystal polymer, typically, a copolymer having a monomer unit containing a thermotropic liquid crystal fragment side chain and a monomer unit containing a non-liquid crystal fragment side chain is used. When the polymer has a thermotropic liquid crystal fragment in the side chain, the side-chain type liquid crystal polymer can be aligned when the liquid crystal composition is heated to a predetermined temperature. When the side-chain type polymer has a non-liquid crystal fragment in the side chain, the non-liquid crystal fragment can interact with the photopolymerizable liquid crystal monomer to homeotropically align the photopolymerizable liquid crystal monomer.
[0047] As the side-chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystalline monomer unit represented by general formula (I) and a non-liquid crystalline monomer unit represented by general formula (II) is preferably used. [ka] [ka]
[0048] In formula (I), R 1 is a hydrogen atom or a methyl group, and R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms; X 1 is -CO2- or -OCO-. a is an integer of 1 to 6, and b and c are each independently 1 or 2.
[0049] In formula (II), R 3 is a hydrogen atom or a methyl group, and R 4 is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III). [ka]
[0050] In formula (III), R5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.
[0051] The ratio of the liquid crystal monomer unit and the non-liquid crystal monomer unit in the side chain type liquid crystal monomer can be appropriately set according to the purpose. The ratio (molar ratio) of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.
[0052] The ratio of the liquid crystal monomer to the side-chain liquid crystal polymer in the liquid crystal composition can be appropriately set depending on the purpose. When the content of the side-chain liquid crystal polymer is high, the Nz coefficient tends to be small; when the content of the liquid crystal monomer is high, the Nz coefficient tends to be small. The content of the liquid crystal monomer is preferably 1.2 to 20 times, more preferably 1.3 to 10 times, further preferably 1.4 to 9 times, and particularly preferably 1.5 to 8 times, the content of the side-chain liquid crystal polymer. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.
[0053] Details of the side-chain liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921, the disclosure of which is incorporated herein by reference.
[0054] The retardation layer 20 may further include a positive C plate. The refractive index characteristic of the positive C plate is in the relationship of nz>nx=ny. The thickness direction retardation Rth(550) of the positive C plate is preferably -20 nm to -300 nm, more preferably -30 nm to -250 nm, further preferably -40 nm to -200 nm, and particularly preferably -50 nm to -150 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the positive C plate may be less than 10 nm.
[0055] The positive C plate can be formed, for example, using a composition containing the above-mentioned side-chain liquid crystal polymer. Specific examples of the method for forming the positive C plate include the methods described in
[0020] to
[0028] of JP 2002-333642 A. In this case, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0056] D. Adhesive layer The adhesive layer 30 may have any appropriate configuration as long as it achieves the desired thickness variation and / or the desired T×S. The adhesive layer 30 may typically be made of an active energy ray-curable adhesive, as described above.
[0057] Any suitable active energy ray curable adhesive can be used as the active energy ray curable adhesive. Examples of the active energy ray curable adhesive include ultraviolet ray curable adhesives and electron beam curable adhesives. In addition, from the viewpoint of the curing mechanism, examples of the active energy ray curable adhesive include radical curable adhesives, cationic curable adhesives, anionic curable adhesives, and hybrids of radical curable adhesives and cationic curable adhesives. Typically, a radical curable ultraviolet ray curable adhesive can be used. This is because it is versatile and the properties (composition) can be easily adjusted.
[0058] The active energy ray curable adhesive typically contains a monofunctional component, a polyfunctional component (curing component), and a photopolymerization initiator. The monofunctional component and the polyfunctional component are typically radical polymerizable compounds. Preferred monofunctional components include, for example, higher alkyl esters of (meth)acrylic acid and modified products thereof. Specific examples include isostearyl acrylate, lauryl acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and the like. By using such monofunctional components having a large molecular weight per functional group, an adhesive with a small cure shrinkage rate can be obtained. As a result, an adhesive layer with a small thickness variation can be obtained. Preferred polyfunctional components include, for example, monomers and / or oligomers having two or more functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples include polyethylene glycol diacrylate, trimethylpropane triacrylate, and glycerin triacrylate. Specific examples of monofunctional or polyfunctional components other than those mentioned above include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-methylol acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, 9-vinyl carbazole, 4-vinyl phenyl boronic acid, and fluorene-based acrylates. In one embodiment, the monofunctional or polyfunctional component has a ring structure. Specific examples include acryloyl morpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, 9-vinyl carbazole, and fluorene-based acrylates. Compounds having a ring structure have a small free volume (high density), so the use of such compounds can provide an adhesive with a small cure shrinkage rate, which can result in an adhesive layer with small thickness variations.The monofunctional component or the polyfunctional component may each be used alone or in combination of two or more kinds.
[0059] The active energy ray curable adhesive may further contain a cationic polymerizable compound as required. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of the monofunctional cationic polymerizable compound include p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane. Examples of the polyfunctional cationic polymerizable compound include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane. A silane coupling agent may be used as the cationic polymerizable compound. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane.
[0060] The active energy ray curable adhesive may further contain an acrylic oligomer as necessary. The molecular weight of the acrylic oligomer may be appropriately set according to the purpose. By using an acrylic oligomer that does not form additional bonds, an adhesive with a small cure shrinkage rate can be obtained. As a result, an adhesive layer with a small thickness variation can be obtained.
[0061] The active energy ray-curable adhesive may further contain a photopolymerization initiator as necessary. Examples of the photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, and diethylthioxanthone.
[0062] The active energy ray-curable adhesive may further contain a plasticizer (for example, an oligomer component), a crosslinking agent, a diluent, etc., depending on the purpose. Commercially available products may be used for each of the above components.
[0063] It is preferable that the absolute value of the difference between the refractive index of the active energy ray-curable adhesive and that of the adjacent layer (particularly, the first liquid crystal alignment solidified layer) is as small as possible.
[0064] Details of the active energy ray-curable adhesive are described, for example, in JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.
[0065] E. Interlayer adhesive layer E-1.Overview As described above, the interlayer adhesive layer (not shown) is an adhesive layer for laminating the first liquid crystal alignment solidified layer 21 and the second liquid crystal alignment solidified layer 22. The interlayer adhesive layer may be made of a pressure sensitive adhesive or an adhesive.
[0066] In one embodiment, the refractive index n LC1 , the refractive index n of the second liquid crystal alignment solidified layer LC2 , and the refractive index of the interlayer adhesive layer, n AD , and the thickness T of the interlayer adhesive layer AD and thickness variation TV AD satisfies the following formula (1). The left side of formula (1) may be referred to as the display unevenness parameter. In this specification, the "refractive index" of the liquid crystal alignment solidified layer means the refractive index in the transmission axis direction of the polarizer, unless otherwise specified. Since the adhesive layer is substantially optically isotropic, the refractive index n AD is also isotropic. |{(n LC1 +n LC2 ) / 2-n AD}|×(TV AD / T AD ) × 1000≦3.0 (1) The display unevenness parameter is preferably 2.5 or less, more preferably 2.0 or less, even more preferably 1.8 or less, particularly preferably 1.2 or less, and particularly preferably 0.7 or less. The smaller the display unevenness parameter (absolute value), the more preferable it is, and it can be, for example, 0.0.
[0067] Regardless of whether the interlayer adhesive layer is an adhesive layer or a pressure-sensitive adhesive layer, the refractive index n ADThe refractive index n of the interlayer adhesive layer may be, for example, 1.45 or more, or may be, for example, 1.50 or more, or may be, for example, 1.52 or more. AD is preferably 1.54 or more, more preferably 1.55 or more, further preferably 1.57 or more, and particularly preferably 1.60 or more. On the other hand, the refractive index n AD can be, for example, 1.63 or less.
[0068] When the interlayer adhesive layer is a pressure-sensitive adhesive layer, the thickness T of the interlayer adhesive layer AD is, for example, 3 μm or more, preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and particularly preferably 15 μm or more. AD When the interlayer adhesive layer is an adhesive layer, the thickness T AD The thickness variation TV of the interlayer adhesive layer is preferably 0.5 μm to 2.0 μm, and more preferably 0.8 μm to 1.2 μm. AD is preferably 0.20 μm or less, more preferably 0.18 μm or less, and further preferably 0.16 μm or less. AD can be, for example, 0.03 μm or more.
[0069] The pressure-sensitive adhesive and the adhesive constituting the interlayer adhesive layer will be described below.
[0070] E-2. Adhesive Any suitable structure may be adopted as the adhesive as long as it satisfies the above characteristics. Specific examples of adhesives include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base polymer of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired characteristics according to the purpose can be prepared. The base polymer of the adhesive may be used alone or in combination of two or more. From the viewpoints of transparency, processability, durability, and the like, an acrylic adhesive (acrylic adhesive composition) is preferred. The acrylic adhesive composition typically contains a (meth)acrylic polymer as the base polymer as the main component. The (meth)acrylic polymer may be contained in the adhesive composition at a ratio of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the adhesive composition. In addition, (meth)acrylate refers to acrylate and / or methacrylate.
[0071] The (meth)acrylic polymer preferably contains an aromatic ring-containing monomer (m1) as a monomer component. As the monomer (m1), a compound containing at least one aromatic ring and at least one ethylenically unsaturated group in one molecule can be used. As the monomer (m1), such a compound may be used alone or in combination of two or more kinds. The aromatic ring and the ethylenically unsaturated group may be bonded directly or via a linking group.
[0072] Examples of the ethylenically unsaturated group include a (meth)acryloyl group, a vinyl group, and a (meth)allyl group. In terms of polymerization reactivity, a (meth)acryloyl group is preferred, and in terms of flexibility and adhesiveness, an acryloyl group is more preferred. In terms of suppressing a decrease in the flexibility of the adhesive, a compound having one ethylenically unsaturated group in one molecule (i.e., a monofunctional monomer) is preferably used as the monomer (m1).
[0073] The number of aromatic rings contained in one molecule of the compound used as monomer (m1) may be 1 or 2 or more. The upper limit of the number of aromatic rings contained in monomer (m1) is not particularly limited, and may be, for example, 16 or less. In some embodiments, from the viewpoint of ease of preparation of the (meth)acrylic polymer and transparency of the pressure-sensitive adhesive, the number of aromatic rings may be, for example, 12 or less, preferably 8 or less, more preferably 6 or less, may be 5 or less, 4 or less, 3 or less, or may be 2 or less.
[0074] The aromatic ring of the compound used as the monomer (m1) may be, for example, a carbon ring such as a benzene ring (which may be a benzene ring constituting a part of a biphenyl structure or a fluorene structure); a condensed ring of a naphthalene ring, an indene ring, an azulene ring, an anthracene ring, or a phenanthrene ring; or may be, for example, a pyridine ring, a pyrimidine ring, a pyridazine ring, a pyrazine ring, a triazine ring, a pyrrole ring, a pyrazole ring, an imidazole ring, a triazole ring, an oxazole ring, an isoxazole ring, a thiazole ring, or a thiophene ring. The heteroatom contained as a ring-constituting atom in the heterocycle may be, for example, one or more selected from the group consisting of nitrogen, sulfur, and oxygen. In some embodiments, the heteroatom constituting the heterocycle may be one or both of nitrogen and sulfur. The monomer (m1) may have a structure in which one or more carbon rings and one or more heterocycles are condensed, such as a dinaphthothiophene structure.
[0075] Examples of compounds that can be preferably used as the monomer (m1) include aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds. The aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds can be used alone or in combination of two or more. One or more aromatic ring-containing (meth)acrylates and one or more aromatic ring-containing vinyl compounds can be used in combination.
[0076] The content of the monomer (m1) in the monomer components constituting the (meth)acrylic polymer can be set so as to realize a pressure-sensitive adhesive layer that has both the desired refractive index and adhesive properties (e.g., peel strength, flexibility, etc.) and / or optical properties (e.g., total light transmittance, haze value, etc.). In some embodiments, the content of the monomer (m1) in the monomer components may be, for example, 30% by weight or more, preferably 50% by weight or more, 60% by weight or more, or 70% by weight or more. From the viewpoint of easily obtaining a higher refractive index, in some embodiments, the content of the monomer (m1) may be, for example, more than 70% by weight, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. The upper limit of the content of the monomer (m1) in the monomer components is 100% by weight. From the viewpoint of achieving a good balance between a high refractive index and adhesive properties and / or optical properties, the content of the monomer (m1) is advantageously less than 100% by weight, and is preferably about 99% by weight or less, more preferably 98% by weight or less, and may be 97% by weight or less, or may be 96% by weight or less. In some embodiments, the content of the monomer (m1) may be 93% by weight or less, 90% by weight or less, 80% by weight or less, or 75% by weight or less. In some embodiments that place more importance on adhesive properties and / or optical properties, the content of the monomer (m1) in the monomer component may be 70% by weight or less, 60% by weight or less, or 45% by weight or less.
[0077] In some embodiments, as the monomer (m1), a monomer having two or more aromatic rings (preferably carbon rings) in one molecule can be preferably used because it is easy to obtain a high refractive index effect. Examples of a monomer having two or more aromatic rings in one molecule (hereinafter also referred to as a "monomer containing multiple aromatic rings") include a monomer having a structure in which two or more non-condensed aromatic rings are bonded via a linking group, a monomer having a structure in which two or more non-condensed aromatic rings are chemically bonded directly (i.e., without other atoms), a monomer having a condensed aromatic ring structure, a monomer having a fluorene structure, a monomer having a dinaphthothiophene structure, a monomer having a dibenzothiophene structure, and the like. The monomer containing multiple aromatic rings may be used alone or in combination of two or more.
[0078] A high refractive index monomer may be preferably used as at least a part of the monomer (m1). Here, the term "high refractive index monomer" refers to a monomer having a refractive index of, for example, about 1.510 or more, preferably about 1.530 or more, more preferably about 1.550 or more. The upper limit of the refractive index of the high refractive index monomer is not particularly limited, but from the viewpoint of ease of preparation of the adhesive composition and ease of compatibility with flexibility suitable for an adhesive, it may be, for example, 3.000 or less, 2.500 or less, 2.000 or less, 1.900 or less, 1.800 or less, or 1.700 or less. The high refractive index monomer may be used alone or in combination of two or more kinds. The refractive index of the monomer can be measured, for example, using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25° C. As the Abbe refractometer, a model "DR-M4" manufactured by ATAGO or an equivalent product can be used. When the manufacturer provides a nominal value of the refractive index at 25° C., that nominal value can be used.
[0079] As the high refractive index monomer, a compound having a corresponding refractive index can be appropriately selected from among the compounds (for example, the compounds and compound groups exemplified above) included in the concept of the aromatic ring-containing monomer (m1). Specific examples include m-phenoxybenzyl acrylate (refractive index: 1.566, homopolymer Tg: -35°C), 1-naphthylmethyl acrylate (refractive index: 1.595, homopolymer Tg: 31°C), ethoxylated o-phenylphenol acrylate (repeated number of oxyethylene units: 1, refractive index: 1.578), benzyl acrylate (refractive index (nD20): 1.519, homopolymer Tg: 6°C), phenoxyethyl acrylate (refractive index (nD20): 1.517, homopolymer Tg: 2°C), phenoxydiethylene glycol acrylate (refractive index: 1.51 0, homopolymer Tg: -35°C), 6-acryloyloxymethyldinaphthothiophene (6MDNTA, refractive index: 1.75), 6-methacryloyloxymethyldinaphthothiophene (6MDNTMA, refractive index: 1.726), 5-acryloyloxyethyldinaphthothiophene (5EDNTA, refractive index: 1.786), 6-acryloyloxyethyldinaphthothiophene (6EDNTA, refractive index: 1.722), 6-vinyldinaphthothiophene (6VDNT, refractive index: 1.802), and 5-vinyldinaphthothiophene (abbreviation: 5VDNT, refractive index: 1.793).
[0080] The content of the high refractive index monomer in the monomer (m1) (i.e., an aromatic ring-containing monomer having a refractive index of about 1.510 or more, preferably about 1.530 or more, more preferably about 1.550 or more) is not particularly limited, and may be, for example, 5% by weight or more, 25% by weight or more, 35% by weight or more, or 40% by weight or more. In some embodiments, from the viewpoint of easily obtaining a higher refractive index, the content of the high refractive index monomer in the monomer (m1) may be, for example, 50% by weight or more, preferably 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m1) may be a high refractive index monomer. In some embodiments, for example, from the viewpoint of achieving a good balance between high refractive index and adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be less than 100% by weight, 98% by weight or less, 90% by weight or less, 80% by weight or less, or 65% by weight or less. In some embodiments, taking into consideration adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be 70% by weight or less, 50% by weight or less, 25% by weight or less, 15% by weight or less, or 10% by weight or less. The embodiment of the present invention may be feasible even if the content of the high refractive index monomer in the monomer (m1) is less than 5% by weight. It is not necessary to use a high refractive index monomer.
[0081] The (meth)acrylic polymer may contain, as a monomer component, a monomer (copolymerizable monomer) that is copolymerizable with the aromatic ring-containing monomer (m1). Examples of the copolymerizable monomer include aliphatic alkyl (meth)acrylate, alicyclic alkyl (meth)acrylate, carboxyl group-containing monomer, hydroxyl group-containing monomer, and amide group-containing monomer. The type, number, combination, and content of the copolymerizable monomer in the monomer component may be appropriately set according to the purpose.
[0082] The acrylic adhesive (acrylic adhesive composition) may contain a refractive index enhancer depending on the purpose. In this specification, the refractive index enhancer refers to a material that can increase the refractive index of the adhesive layer by its use. As the refractive index enhancer, a material having a higher refractive index than the refractive index of the adhesive layer containing the refractive index enhancer can be preferably used. In addition, as the refractive index enhancer, a material having a higher refractive index than the base polymer (e.g., acrylic polymer) of the adhesive layer containing the refractive index enhancer can be preferably used. By appropriate use of the refractive index enhancer, a higher refractive index and practical adhesive performance can be suitably achieved at the same time. In some embodiments, the refractive index enhancer is preferably an organic material. The organic material used as the refractive index enhancer may be a polymer or a non-polymer. In addition, it may or may not have a polymerizable functional group. The refractive index enhancer may be used alone or in combination of two or more kinds.
[0083] The amount of the refractive index enhancer used relative to 100 parts by weight of the base polymer (when a plurality of types of refractive index enhancers are used, the total amount of them) can be appropriately set according to the purpose. From the viewpoint of increasing the refractive index of the adhesive, the amount of the refractive index enhancer used relative to 100 parts by weight of the base polymer can be, for example, 1 part by weight or more, advantageously 3 parts by weight or more, preferably 5 parts by weight or more, may be 7 parts by weight or more, may be 10 parts by weight or more, may be 15 parts by weight or more, or may be 20 parts by weight or more. In some embodiments, the amount of the refractive index enhancer used relative to 100 parts by weight of the base polymer can be, for example, 80 parts by weight or less, and from the viewpoint of achieving a good balance between increasing the refractive index of the adhesive and suppressing the deterioration of adhesive properties and optical properties, it is advantageous to set it to 60 parts by weight or less, and preferably to set it to 45 parts by weight or less. In some embodiments that place more importance on adhesive properties and optical properties, the amount of the refractive index enhancer used relative to 100 parts by weight of the base polymer may be, for example, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less. The embodiment of the present invention may be implemented even if the amount of the refractive index enhancer used relative to 100 parts by weight of the base polymer in the adhesive layer is less than 1 part by weight, or even if the refractive index enhancer is not substantially used. Here, "substantially not used" means that at least not used intentionally.
[0084] (Additives (H RO )) In some embodiments, an organic material having a higher refractive index than the base polymer may be preferably used as the refractive index enhancer. Hereinafter, such an organic material will be referred to as an "additive (H RO )" where "H RO " indicates that it is an organic material with a high refractive index. RO ) may be used alone or in combination of two or more.
[0085] Additives (H ROExamples of organic materials that can be selected for the additive (H) include organic compounds having an aromatic ring and organic compounds having a heterocycle (which may be an aromatic ring or a non-aromatic heterocycle). RO The aromatic ring contained in the organic compound having an aromatic ring (hereinafter also referred to as "aromatic ring-containing compound") used as monomer (m1) can be selected from the same aromatic rings contained in the compound used as monomer (m2).
[0086] Additives (H RO ) may be used, but are not limited to, aromatic ring-containing monomers such as benzyl acrylate, m-phenoxybenzyl acrylate, 2-(o-phenylphenoxy)ethyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, the above-mentioned monomers having a fluorene structure, monomers having a dinaphthothiophene structure, and monomers having a dibenzothiophene structure; and aromatic ring-containing compounds not having an ethylenically unsaturated group, such as 3-phenoxybenzyl alcohol, dinaphthothiophene and derivatives thereof (for example, compounds having a structure in which one or more of one or more substituents selected from a hydroxyl group, a methanol group, a diethanol group, a glycidyl group, and the like are bonded to a dinaphthothiophene ring).
[0087] The acrylic adhesive composition may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an additive. Specific examples of the additive include antioxidants, conductive agents, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils. In addition, a redox system may be adopted by adding a reducing agent within a controllable range. The type, number, combination, content, etc. of the silane coupling agent, crosslinking agent, and / or additives may be appropriately set according to the purpose.
[0088] E-3. Adhesive The adhesive (adhesive composition) may typically contain an aromatic ring skeleton-containing (meth)acrylate and metal oxide particles. Each will be briefly described below. Note that other components (e.g., curing component, pressure-sensitive adhesive) that may be contained in the adhesive may have a well-known configuration, so a detailed description will be omitted.
[0089] By containing the (meth)acrylate having an aromatic ring skeleton in the adhesive composition, an adhesive layer having a desired refractive index can be formed in the embodiment of the present invention. As the (meth)acrylate having an aromatic ring skeleton, it is preferable to use at least one selected from the group consisting of (meth)acrylates having a polycyclic aromatic ring skeleton and (meth)acrylates having two or more aromatic rings. Examples of such (meth)acrylates include benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 1-naphthalenemethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, ethylene oxide modified orthophenylphenol (meth)acrylate, and a reaction product of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene and (meth)acrylic acid. Among these, it is more preferable to use phenoxybenzyl (meth)acrylate and phenoxyethyl (meth)acrylate, and it is particularly preferable to use phenoxybenzyl (meth)acrylate. The amount of the (meth)acrylate having an aromatic ring skeleton is preferably 20% by mass to 90% by mass, and more preferably 30% by mass to 80% by mass, when the total amount of the adhesive composition is 100% by mass.
[0090] Examples of metal oxide particles include silicon oxide, zirconium oxide, titanium oxide, zinc oxide, antimony pentoxide, tin oxide, aluminum oxide, indium oxide, indium tin oxide, ferric oxide, cerium oxide, yttrium oxide, manganese oxide, holmium oxide, copper oxide, bismuth oxide, cobalt oxide, tricobalt tetraoxide, triferric oxide, magnesium oxide, lanthanum oxide, praseodymium oxide, neodymium oxide, samarium oxide, eurobium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, erbium oxide, thulium oxide, ytterbium oxide, lutetium oxide, scandium oxide, tantalum pentoxide, niobium pentoxide, iridium oxide, rhodium oxide, ruthenium oxide, and composite oxides that combine these.Among these, zirconium oxide and titanium oxide are preferred, and zirconium oxide is particularly preferred. The metal oxide particles may be composed of only the metal oxides listed above, or may contain other components, but it is preferable that the metal oxides account for the largest proportion by weight of the components in the particles. The shape of the metal oxide particles may be any shape, such as a sphere, an elliptical sphere, a cube, a rectangular parallelepiped, or a pyramid. The metal oxide particles may be surface-treated by any suitable method.
[0091] From the viewpoint of improving the stability of the metal oxide particles in the adhesive composition and improving the refractive index of the adhesive layer, the average particle size of the metal oxide particles is preferably 1 nm to 150 nm, and more preferably 1 nm to 50 nm. The average particle size of the metal oxide particles can be derived, for example, by the following method: observing the particles under magnification using a transmission electron microscope (TEM), a field emission transmission electron microscope (FE-TEM), a field emission scanning electron microscope (FE-SEM), or the like, randomly selecting, for example, 1000 particles, measuring their maximum length, and calculating the arithmetic average.
[0092] From the standpoint of improving the stability of the metal oxide particles in the adhesive composition and improving the refractive index of the adhesive layer, the amount of the metal oxide particles is preferably 10% by mass to 50% by mass, and more preferably 15% by mass to 40% by mass, when the total amount of the adhesive composition is 100% by mass.
[0093] The adhesive composition may further contain a hydroxyl group-containing (meth)acrylate. With such a configuration, the adhesive strength of the adhesive layer can be further improved. The amount of the hydroxyl group-containing (meth)acrylate blended is preferably 1% by mass to 30% by mass, and more preferably 3% by mass to 20% by mass, when the total amount of the adhesive composition is taken as 100% by mass.
[0094] F. Image display device The optical laminate described in the above items A to E can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device using such an optical laminate. Representative examples of the image display device include a liquid crystal display device and an organic EL display device. The image display device according to the embodiment of the present invention typically includes the optical laminate described in the above items A to E on the viewing side. EXAMPLES
[0095] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Measurement and evaluation methods in the examples are as follows. Unless otherwise specified, "parts" and "%" in the examples are based on weight.
[0096] (1) Curing shrinkage rate Measurements were performed in accordance with JIS K 6941 using a resin cure shrinkage measuring device (manufactured by Acroedge Co., Ltd., product name "CUSTRON EU201C"). Specifically, the procedure is as follows: Uncured adhesives used in the examples and comparative examples were placed in a cylindrical container with an inner diameter of 15 mm and a depth of 3 mm to a thickness of T0. 1000 mJ / cm2 was applied to the adhesive in the container. 2 The adhesive is cured by irradiating it with ultraviolet light, and the cured thickness is T DThe hardening shrinkage was calculated from the following formula: Curing shrinkage rate (%)={(T0-T D ) / T0}×100
[0097] (2) Thickness The thickness was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., "MCPD9800").
[0098] (3) Thickness variation For the laminate of the polarizing plate / adhesive layer / first liquid crystal alignment solidified layer in the optical laminate obtained in the examples and comparative examples, thickness mapping measurements were performed at 1 mm pitch in an area of 10 cm x 10 cm using "USB4H09646" manufactured by Ocean Optics Co., Ltd. The thickness difference at the point where the thickness difference between three adjacent points was the largest was taken as the thickness variation.
[0099] (4) Linear unevenness A normal acrylic adhesive was placed on the second liquid crystal alignment solidified layer side of the optical laminate obtained in the examples and comparative examples, and the optical laminate was attached to a V3 reflector (manufactured by NEODIS) via the acrylic adhesive to prepare a test sample. The obtained test sample was visually observed under a three-wavelength fluorescent lamp and evaluated according to the following criteria. 1: No linear unevenness was observed 2: Slight linear irregularities were observed 3: Linear unevenness was observed, but was within practical acceptable limits 4: Linear unevenness was observed to an extent that was practically unacceptable. 5: Linear unevenness was noticeable
[0100] [Production Example 1: Preparation of Adhesive A for Laminating Polarizing Plate and Retardation Layer] Adhesive A was prepared by stirring 40 parts of hydroxyethyl acrylamide (trade name "HEAA", manufactured by KJ Chemicals), 32 parts of acryloyl morpholine (trade name "ACMO", manufactured by KJ Chemicals), 25 parts of tripropylene glycol diacrylate (trade name "Aronix M-220"), 1 part of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", manufactured by IGM Resins BV), 2 parts of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins BV), and 1 part of diethylthioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) at 50°C for 1 hour.
[0101] [Production Example 2: Preparation of Adhesive B for Laminating Polarizing Plate and Retardation Layer] Hydroxyethyl acrylamide (trade name "HEAA", KJ Chemicals) 10 parts, 2-acetoacetoxyethyl methacrylate (trade name "AAEM", Mitsubishi Chemicals) 4 parts, acryloylmorpholine (trade name "ACMO", KJ Chemicals) 60 parts, tripropylene glycol diacrylate (trade name "Aronix M-220") 11 parts, 4-vinylphenylboronic acid (Fujifilm Wako Pure Chemical Industries) 1 part, acrylic oligomer (trade name "ARUFON UP-1190", Toagosei) 10 parts, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", IGM Resins BV) 1 part, 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", IGM Resins Adhesive B was prepared by stirring 2 parts of ethyl thioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) and 1 part of diethylthioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) at 50° C. for 1 hour.
[0102] [Production Example 3: Preparation of Adhesive C for Laminating Polarizing Plate and Retardation Layer] 60 parts of OGSOL EA-F5710 (Osaka Gas Chemicals Co., Ltd.), 10 parts of PLAXEL FA1DDM (Daicel Corporation), 20 parts of acryloylmorpholine (trade name "ACMO", KJ Chemicals Co., Ltd.), 5 parts of acrylic oligomer (trade name "ARUFON UP-1190", Toagosei Co., Ltd.), 1 part of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", IGM Resins BV), 2 parts of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", IGM Resins BV), and 2 parts of diethylthioxanthone (trade name "KAYACURE DETX-S", Nippon Kayaku Co., Ltd.) were stirred at 50°C for 1 hour to prepare adhesive C.
[0103] [Example 1] 1. Preparation of Polarizing Plates 1-1. Preparation of polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0104] 1-2. Preparation of polarizing plate An HC-COP film was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curable adhesive. The HC-COP film was a film in which an HC layer (thickness 4 μm) was formed on a cycloolefin resin (COP) film (thickness 25 μm), and the COP film was attached to the polarizer side. The COP film had a Re(550) of 135 nm. Next, the resin substrate was peeled off to obtain a polarizing plate having a configuration of HC layer / COP film (protective layer) / polarizer.
[0105] 2. Preparation of retardation layer A photopolymerizable liquid crystal compound exhibiting a nematic liquid crystal phase (BASF's "Paliocolor LC242", chemical formula below) was dissolved in cyclopentanone to prepare a solution with a solid concentration of 30% by weight. A surfactant (BYK-Chemie's "BYK-360") and a photopolymerization initiator (IGM Resins' "Omnirad907") were added to this solution to prepare a liquid crystal composition solution. The amounts of the surfactant and polymerization initiator added were 0.01 parts by weight and 3 parts by weight, respectively, per 100 parts by weight of the photopolymerizable liquid crystal compound. A biaxially stretched norbornene-based film (Zeon Corporation's "ZEONOR Film", thickness 33 μm, Re(550)=135 nm) was prepared as a substrate. The above liquid crystal composition was applied to this substrate with a bar coater so that Re(550) was 240 nm, and the liquid crystal was aligned by heating at 100°C for 3 minutes. After cooling to room temperature, the device was placed in a nitrogen atmosphere with an integrated light dose of 400 mJ / cm 2 The laminate was irradiated with ultraviolet light of 1000 nm to photo-cure the film, and a laminate having a structure of a substrate / first liquid crystal alignment solidified layer was obtained. The first liquid crystal alignment solidified layer had a homogeneous alignment and a thickness of 1.7 μm. A laminate of a substrate / second liquid crystal alignment solidified layer (homogeneous alignment, thickness 0.92 μm, Re(550)=130 nm) was obtained in the same manner as above, except that the coating thickness was changed. [ka]
[0106] 3. Preparation of Optical Laminate The first liquid crystal alignment solidified layer was attached to the polarizer surface of the polarizing plate via the adhesive A (thickness 1.2 μm) of Manufacturing Example 1, and then the substrate was peeled off. Next, the second liquid crystal alignment solidified layer was attached to the surface of the first liquid crystal alignment solidified layer via an acrylic adhesive (5 μm, refractive index 1.47), and the substrate was peeled off to obtain an optical laminate having a configuration of polarizing plate / adhesive layer / first liquid crystal alignment solidified layer / interlayer adhesive layer / second liquid crystal alignment solidified layer. In the optical laminate, the angle between the transmission axis of the polarizer of the polarizing plate and the slow axis of the first liquid crystal alignment solidified layer was 15°, and the angle between the transmission axis of the polarizer of the polarizing plate and the slow axis of the second liquid crystal alignment solidified layer was 75°. The obtained optical laminate was subjected to the evaluation of the above-mentioned "linear unevenness". The results are shown in Table 1.
[0107] [Examples 2 to 12 and Comparative Examples 1 to 6] An optical laminate was obtained in the same manner as in Example 1, except that the configuration of the adhesive layer was changed as shown in Table 1. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0108] [Table 1] [Industrial Applicability]
[0109] The optical laminate according to the embodiment of the present invention can be suitably used in image display devices (typically, liquid crystal display devices and organic EL display devices). [Explanation of symbols]
[0110] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 20 Retardation layer 21 First liquid crystal alignment solidification layer 22 Second liquid crystal alignment solidification layer 30 Adhesive layer 100 Optical laminate
Claims
1. A polarizing plate including a polarizer and a retardation layer laminated on the polarizing plate via an adhesive layer, the retardation layer includes, in order from the polarizing plate side, a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer, the retardation layer as a whole has a circular polarization function or an elliptically polarizing function and has a relationship of Re(450)<Re(550)<Re(650); The thickness variation of the adhesive layer in a 10 cm x 10 cm area is 0.16 μm or less. Optical laminate.
2. A polarizing plate including a polarizer and a retardation layer laminated on the polarizing plate via an adhesive layer, the retardation layer includes, in order from the polarizing plate side, a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer, the retardation layer as a whole has a circular polarization function or an elliptically polarizing function and has a relationship of Re(450)<Re(550)<Re(650); When the thickness of the adhesive layer is T (μm) and the cure shrinkage rate of the adhesive constituting the adhesive layer is S (%), T x S ≦ 17 Satisfying Optical laminate.
3. 3. The optical laminate according to claim 2, wherein the adhesive layer has a thickness variation of 0.16 μm or less in an area of 10 cm×10 cm.
4. 4. The optical laminate according to claim 1, wherein the adhesive layer is made of an active energy ray-curable adhesive.
5. The optical laminate according to claim 1 , wherein the first liquid crystal alignment solidified layer has a thickness of 1.7 μm or less.
6. An image display device comprising the optical laminate according to claim 1 .
Citation Information
Patent Citations
Polarizing plate with retardation layer
JP2007226016A
Curable resin composition for optical film, optical film and method of manufacturing the same
JP2018087968A
Retardation film with adhesive layer, polarizing plate with retardation layer, and method of manufacturing retardation film with adhesive layer
JP2021047235A
Manufacturing method of alignment liquid crystal film
JP2022144069A
Polarizing plate with retardation layer, and image display device using the same
JP2023075790A
Cited By
Optical laminate, optical laminate with polarizing film, and image display device
WO2026116029A1